211k views
2 votes
Ayyy, wassup people! can y'all do my homework? Imma reward you.

1. Simplify Fully
(x+3)/(4)+(x-5)/(3)
2.Write
(1)/(x+4)+(2)/(x-4) as a single fraction in it's simplest form.

User Falico
by
4.2k points

2 Answers

6 votes

Answer:

1) (7x-11)/12

2) (3x+4)/(x²-16)

Explanation:

1)

(x+3)/4 + (x-5)/3

Lcm: 12

[3(x+3) + 4(x-5)]/12

(3x+4x+9-20)/12

(7x-11)/12

2) 1/(x+4) + 2/(x-4)

Lcm: (x+4)(x-4) = x²-16

[(x-4)(1) + (x+4)(2)]/(x²-16)

(x-4+2x+8)/(x²-16)

(3x+4)/(x²-16)

User Kovo
by
4.3k points
3 votes

Answer and Step-by-step explanation:


Good~Day!


Let's~answer~your~question~shall~we?

Answer for the first question:


=(3(x+3))/(12) +(4(x-5))/(12)


=(x(x+3)~+~4(x-5))/(12)


=(3x+~9+~4x~4-20)/(12)


=(7x~-~11)/(12)

Answer:


(7x~-~11)/(12)

________________________________________________

Answer for the second question:


(x-4)/((x+4)~(x-4)) ~+ ~(2(x+4))/((x+4)~(x-4))


=(x-4~+~2~(x+4))/((x+4)~(x-4)) =(x-4~+~2x~+8)/((x+4)~(x-4))


=(3x~+~4)/((x+4)~(x-4))

Answer:


(3x~+~4)/((x+4)~(x-4))

User Flaschbier
by
5.2k points